2018
DOI: 10.1007/s12178-018-9460-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Injuries to the Biceps and Superior Labral Complex in Overhead Athletes

Abstract: A focused patient history, numerous physical examination maneuvers, and appropriate advanced imaging studies must be utilized to reach an accurate diagnosis. Nonoperative management, even in overhead athletes, has demonstrated relatively good outcomes, while operative outcomes have yielded mixed results. The surgeon must take into account a number of variables when choosing the appropriate surgical procedure: labral repair versus biceps tenodesis. Rehabilitation, either as nonoperative management or as a posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…However, broader sutures such as labral tape may have the benefit of increased strength while restoring labral height and allowing for a broader surface of compression, thus limiting "cut-through" on the labrum. 31 Furthermore, the technique or type of suture passage could be important and not often reported upon (Figs 3 and 4 A and B).…”
Section: Discussionmentioning
confidence: 99%
“…However, broader sutures such as labral tape may have the benefit of increased strength while restoring labral height and allowing for a broader surface of compression, thus limiting "cut-through" on the labrum. 31 Furthermore, the technique or type of suture passage could be important and not often reported upon (Figs 3 and 4 A and B).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of successful repair of SLAP lesions has been reported to be as low as 74% 66 . The decrease in primary SLAP repair has come with a concurrent increase in biceps tenotomy and tenodesis procedures 41,66,67 . The literature has demonstrated that both procedures result in similar postoperative functional outcomes, including pain, stiffness, mobility, and strength 41,68,69 .…”
Section: Decision-making For Bicipital-labral Complex Injuriesmentioning
confidence: 99%
“…Shoulder pain related to biceps-labrum complex (BLC) disease, which includes superior labral anterior and posterior (SLAP) tears, long head of the biceps tendon (LHBT) instability, and proximal LHBT tearing, is a frequent clinical dilemma. 2 Tenodesis of the LHBT is a common procedure to address refractory BLC symptoms, including LHBT instability, biceps tendinopathy or tearing, and SLAP tears in some patients, with over 44,000 procedures performed annually and an increasing number of tenodeses performed each year. 11 , 14 Recently, indications for this procedure have expanded to include the treatment of SLAP tears and extra-articular bicipital tunnel disease.…”
mentioning
confidence: 99%